Androgen serum levels in male patients with adrenocortical carcinoma given mitotane therapy: A single center retrospective longitudinal study - Delbarba, Andrea; Cosentini, Deborah; Facondo, Paolo; Laganà, Marta; Pezzaioli, Letizia Chiara; Cremaschi, Valentina; Alberti, Andrea; Grisanti, Salvatore; Cappelli, Carlo; Ferlin, Alberto; Berruti, Alfredo (Frontiers in Endocrinology, 2023)
Objective: hypogonadism is common in male patients with adrenocortical carcinoma (ACC) who are under treatment with mitotane, but the phenomenon is underestimated and its prevalence has been poorly studied. This single center retrospective longitudinal study was undertaken to assess the frequency of testosterone deficiency before and after mitotane therapy, the possible mechanism involved and the relationship between hypogonadism with serum mitotane levels and prognosis. Research Design and Methods: Consecutive male ACC patients followed at medical oncology of Spedali Civili Hospital in Brescia underwent hormonal assessment to detect testosterone deficiency at baseline and during mitotane therapy. Results: twenty-four patients entered the study. Ten of them (41.7%) had already testosterone deficiency at baseline. During follow-up, total testosterone (TT) showed a biphasic evolution over time with an increase in the first six months followed by a subsequent progressive decrease until 36 months. Sex hormone binding globulin (SHBG) progressively increased and calculated free testosterone (cFT) progressively decreased. Based on cFT evaluation the proportion of hypogonadic patients progressively increased with a cumulative prevalence of 87.5% over the study course. A negative correlation was observed between serum mitotane levels > 14 mg/l and TT and cFT. Conclusions: testosterone deficiency is common in men with ACC prior to mitotane treatment; in addition, this therapy exposes these patients to further elevated risk of hypogonadism that should be promptly detected and counteracted since it which might negatively impact on quality of life.